2017
DOI: 10.1515/ncrs-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of (Z)-1-(1,5-dimethyl-1H-pyrazol-3-yl)-3-hydroxy-3-(p-toly)prop-2-en-1-one, C15H16N2O2

Abstract: CCDC no.: 1486977The asymmetric unit of the title crystal structure is shown in the gure. Tables 1 and 2 contain details of the measurement method and a list of the atoms including atomic coordinates and displacement parameters. Source of materialA suspension of metallic sodium (0.4 g; 17.39 mmol) in anhydrous toluene was mixed with ethyl-1,5-dimethyl-1-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…Nevertheless, in present conditions, the reaction leads to formation in 95% yield of the isomer shown in Figure 2. The same observation was noted for our other keto-enol derivatives recently postponed [21][22][23][24][25]. …”
Section: X-ray Crystal Structure Descriptionsupporting
confidence: 86%
“…Nevertheless, in present conditions, the reaction leads to formation in 95% yield of the isomer shown in Figure 2. The same observation was noted for our other keto-enol derivatives recently postponed [21][22][23][24][25]. …”
Section: X-ray Crystal Structure Descriptionsupporting
confidence: 86%
“…In continuation of our recent works in the field of the synthesis of novel β-keto–enol heterocyclic derivatives through efficient and simple routes and of the study of their biological activities, , we report in the present investigation on the synthesis and the properties of a novel series of pyrazoles with the β-keto–enol functionality as powerful moieties especially in fungal activity. To the best of our knowledge, this is the first real study aimed at developing diversified structures of keto–enol pyrazoles.…”
Section: Introductionmentioning
confidence: 91%
“…Accordingly, our previously prepared products were exclusively obtained in the -keto-enol tautomer form, governed by the resonance driving force, as confirmed by XRD. [22][23][24][25][26][27] Herein, as proved by its crystal structure determined from the X-ray diffraction study, compound 10 was also found to exist with the -keto-enol tautomer form.…”
Section: Compounds Chemistrymentioning
confidence: 99%
See 2 more Smart Citations